EUROPEC/EAGE Conference and Exhibition 2009
DOI: 10.2118/119835-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Waterflooding Strategy by Manipulation of Injection Brine Composition

Abstract: As brine composition profoundly influences reservoir wettability and hence microscopic sweep, careful design of injection brine is part of a strategy to improve on oil production in existing and future water flooding projects, in both sandstone and carbonate reservoirs and in combination with follow-up EOR projects. The following results were found:Formation water with higher salinity level correlates to a higher content of multivalent cations. This causes the (sandstone) reservoir wettabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
257
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 440 publications
(270 citation statements)
references
References 24 publications
9
257
0
4
Order By: Relevance
“…This phenomenon is indirectly dependent on the rock surface charge (Schramm et al, 1990). Variations in the surface charge and wettability may lead to inter alia adsorption or/and chemical mobilization (Linghtelm et al, 2009). The rock wettability depends on the stability of an aqueous film between rock surface and oil (Hirasaki, 1997).…”
Section: Theorymentioning
confidence: 99%
“…This phenomenon is indirectly dependent on the rock surface charge (Schramm et al, 1990). Variations in the surface charge and wettability may lead to inter alia adsorption or/and chemical mobilization (Linghtelm et al, 2009). The rock wettability depends on the stability of an aqueous film between rock surface and oil (Hirasaki, 1997).…”
Section: Theorymentioning
confidence: 99%
“…The influence of ionic composition on ion-binding and acid/base interaction is usually called multicomponent ion exchange (MIE). It is still under debate whether EDL repulsion [22][23][24] or MIE 11,21,25 dominates ion-tuned wettability.…”
Section: Introductionmentioning
confidence: 99%
“…With the purpose of enhancing oil recovery, low salinity water (LSW) with adequate composition and salinity is injected into the reservoir, which changes the wetting properties of the reservoir rock into that favoring oil recovery 2), 3) . There are many theories regarding the mechanisms of wettability alteration in presence of LSW which are fine migration 4) , the pH effects 3) , multiple-component ion exchange (MIE) 5) , and wettability modification due to double layer expansion 2), 6) . Ligthelm et al (2009) suggested that the application of LSW results in an expansion of the ionic electrical double layer between the clay and the oil interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…There are many theories regarding the mechanisms of wettability alteration in presence of LSW which are fine migration 4) , the pH effects 3) , multiple-component ion exchange (MIE) 5) , and wettability modification due to double layer expansion 2), 6) . Ligthelm et al (2009) suggested that the application of LSW results in an expansion of the ionic electrical double layer between the clay and the oil interfaces. This causes the oil to be desorbed from the rock surface thus increasing the water wetness 6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation